Comprehensive Insights into Hydroxyurea Treatment for Children with Sickle Cell Disease: A Critical Review - Hadia, Dr. Rajesh (Asian Journal of Pharmaceutics (AJP), 2024)
Sickle cell disease (SCD) poses a significant global health challenge, affecting millions with unique implications for red blood cells and associated complications. This critical review, titled “Comprehensive Insights into Hydroxyurea (HU) therapy for Child with SCD,” rigorously analyzes HU’s safety and efficacy in pediatric SCD patients spanning 2000–2023. Employing meticulous methodologies, data synthesis involves diverse sources such as PubMed, Scopus, and the Cochrane Library, prioritizing relevance and research quality through structured title screening, abstract assessment, and full-text scrutiny. The review focuses on pediatric SCD, ensuring precision and applicability. Rigorous data extraction and specialized analyses assess occurrence rates across regions and populations, guiding clinical decisions and future research. Drawing insights from 14 distinct articles, the review provides a global perspective on HU treatment for pediatric SCD. Inclusive of diverse regions such as the USA, Saudi Arabia, Africa, Nigeria, India, Iran, and Yemen, it explores safety and efficacy across demographics. Varied study designs, including clinical trials, retrospective studies, and observational studies, contribute to a nuanced understanding of HU’s impact. The age-diverse participant range and variable treatment durations enhance comprehensiveness. Consistently positive outcomes demonstrate HU’s efficacy in pediatric SCD, showcasing reductions in crises, transfusions, and hospitalizations, alongside hematological improvements. With a well-established safety profile and minimal short-term adverse effects, HU emerges as a secure therapeutic option. Discussed studies from diverse regions highlight specific contributions to understanding HU therapy. Implications for clinical practice, research, and public health underscore the global need for wider HU availability. Future research should address long-term assessments, optimal dosage guidelines, personalized treatment approaches, and health-care utilization. Despite acknowledged limitations such as potential publication bias and methodological variations, this review, with its global perspective and comprehensive analysis, is a valuable resource for clinicians, researchers, and policymakers. Addressing identified limitations and exploring nuanced aspects are crucial for refining HU’s role in managing pediatric SCD. In conclusion, “Comprehensive Insights into HU Treatment for Child with SCD” sheds light on HU therapy’s multifaceted landscape across diverse studies. Synthesizing data from references articles, it provides a global perspective with consistent positive impacts on pediatric SCD, emphasizing reduced crises, hospitalizations, and transfusions, coupled with hematological improvements. Inclusion of varied study designs and patient cohorts enriches understanding. Despite limitations, this review is a valuable resource, urging further investigations to refine HU’s role in managing pediatric SCD.